PENGARUH KONFLIK PERAN, STRES KERJA, LOCUS OF CONTROL, DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION Studi Kasus pada Kantor Akuntan Publik di Jawa Tengah dan DIY - Kurniawati, Dyan; Rintasari, Nugraheni (Universitas Ahmad Dahlan, 2015)
Public accountant offices have been known of the high level of staff turnover, generally to the new staffs. The turnover level should be decreased work in order to the company has had a change to get the benefit of the work improvement of the staffs. The research aims to test the influence of role conflict, work stress, locus of control, organizational commitment toward the turnover intention on public accountant staffs. The population of the research was public accountants who are working at public accountant offices in Central Java and DIY. The research took the sample using questionnaires. The sampling technique is purposive sampling to the population that was taken by respondent criteria. Based on the criteria, it was obtained that the number of sample was 55 respondents from 13 public accountant offices in Central Java and DIY. The data analysis method is using multiple regression test. The result of analysis showed that the role conflict and the work stress do not give influence toward the turnover intention. However, the locus of control and the organizational commitment give influence toward the turnover intention.